Cardiotrophin-1 as a new metabolic biomarker in women with PCOS - YILDIZHAN, BEGÜM; ARSLAN, GAYE; ANIK İLHAN, GÖKÇE; PEKİN, TANJU (TAYLOR & FRANCIS LTD, 2018)
The objective of this study was to investigate cardiotrophin-1 (CT-1) levels as a new metabolic biomarker in women with polycystic ovary syndrome (PCOS). One hundred consecutive women with PCOS were divided into two groups according to presence of metabolic syndrome as MetS+ and MetS-. Clinical, hormonal and metabolic parameters in addition to CT-1 levels were compared between the groups. Correlation analyses were performed between CT-1 and clinical and metabolic parameters in women with PCOS. One hundred PCOS subjects were enrolled in the study, of which 29 subjects were diagnosed with metabolic syndrome. WHR, systolic and diastolic blood pressures, triglyceride, total cholesterol, HOMA-IR, FAI, FGS and CT-1 levels were significantly higher in the MetS+ group compared with the MetS- group. HDL cholesterol was significantly higher in the MetS- group than the MetS+ one. CT-1 levels were found to be positively correlated with diastolic blood pressure, TG levels and FGS. Cardiotrophin-1 may be a promising new metabolic biomarker in women with PCOS. CT-1 may be beneficial for estimating the risk of long-term adverse health consequences and establishing early intervention and preventation strategies.
Keywords: Polycystic ovary syndrome; cardiotrophin-1; metabolic syndrome; metabolic biomarker; cardiometabolic risk; POLYCYSTIC-OVARY-SYNDROME; PLASMA CARDIOTROPHIN-1; GLUCOSE; DISEASE; RISK